Factors Affecting Fresh Semen Quality in Pasundan Cattle at UPTD BPPIBTSP Ciamis - Oky Susandani; Tri Wahyu Suprayogi; Ratna Damayanti; Anwar Ma'ruf (Universitas Airlangga, 2021)
Background: Pasundan cattle are local cattle native to Indonesia. One way to conserve beef cattle genetics is to use Artificial Insemination technology. The success of Artificial Insemination can be influenced by the quality of semen. Purpose: To determine factors affecting fresh semen quality in Pasundan cattle at UPTD BPPIBTSP Ciamis. Methods: The data were obtained through observations on seven Pasundan bulls in March 2021 towards fresh semen quality and some factors influencing it. The Pasundan bulls observed were seven productive males. Results: The fresh semen quality of Pasundan cattle, such as volume, color, and pH, showed good result,s but the average consistency and concentration of spermatozoa were still below the standard. The factors that can affect the fresh semen quality are the breed of beef cattle, age, body weight, feed, season, exercise, and frequency of semen storage. Conclusion: The determining factors that can cause the consistency and concentration of Pasundan cattle’s spermatozoa at UPTD BPPIBTSP Ciamis are feed and season.